2010
DOI: 10.2174/1874401x01003010087
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Bioenergetics Parameters from Two Spring-Fed Riverine Largemouth Bass Populations

Abstract: This study applies a new bioenergetics modeling framework put forth by Walters and Essington (this volume) which estimates bioenergetics parameters and consumption rates of fishes using commonly collected size-at-age and capture-recapture data from field studies. Bioenergetics model parameters and consumption rates are estimated for two populations of largemouth bass Micropterus salmoides with observed differences in growth patterns. We also compare consumption estimates from the bioenergetics model formulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…However activity costs were also higher because larger lake trout were maladapted to finescale movements associated with finding and consuming smaller prey Sherwood et al, 2002). Similarly, Tetzlaff et al (2010) found that a largemouth bass (Micropterus salmoides) population with insufficient abundance of large prey exhibited a much lower allometric anabolic scaling factor (d) than a nearby population with abundant large prey, presumably because energy densities of prey are insufficient to promote growth and due to increased foraging costs associated with attacking many small prey items. Understanding and appropriately accounting for ontogenetic diet or habitat shifts will be necessary in resolving these issues (e.g.…”
Section: Expressing Growth Curve Parameters In Terms Of Bioenergeticsmentioning
confidence: 97%
“…However activity costs were also higher because larger lake trout were maladapted to finescale movements associated with finding and consuming smaller prey Sherwood et al, 2002). Similarly, Tetzlaff et al (2010) found that a largemouth bass (Micropterus salmoides) population with insufficient abundance of large prey exhibited a much lower allometric anabolic scaling factor (d) than a nearby population with abundant large prey, presumably because energy densities of prey are insufficient to promote growth and due to increased foraging costs associated with attacking many small prey items. Understanding and appropriately accounting for ontogenetic diet or habitat shifts will be necessary in resolving these issues (e.g.…”
Section: Expressing Growth Curve Parameters In Terms Of Bioenergeticsmentioning
confidence: 97%